Grant at Vicksburg : the general and the siege - Ballard, Michael B. (Southern Illinois University Press, 2013)
On May 22, 1863, after two failed attempts to take the city of Vicksburg by assault, Major General Ulysses S. Grant declared in a letter to the commander of the Union fleet on the Mississippi River that "the nature of the ground about Vicksburg is such that it can only be taken by a siege." The 47-day siege of Vicksburg orchestrated by Grant resulted in the eventual surrender of the city and fulfilled a major strategic goal for the Union: command of the Mississippi River for the remainder of the war. In this revealing volume, Michael B. Ballard offers the first in-depth exploration of G.